What if communities held the solutions for universal health coverage? - John C. Reeder; Marie-Paule Kieny; Rosanna Peeling; François Bonnici (BMC, 2019)
Abstract This commentary highlights the value of community-engaged social innovations to advance health care delivery in low- and middle-income countries and to accelerate universal health coverage. It emphasizes the importance of research to guide the innovators on what works, what does not work to make their innovations sustainable and to replicate and scale them up as relevant. It also helps to demonstrate impact and to enhance uptake within the health systems.